Natural Compounds That Target DNA Repair Pathways and Their Therapeutic Potential to Counteract Cancer Cells - Lagunas-Rangel, Francisco Alejandro; Bermúdez-Cruz, Rosa María (Frontiers in Oncology, 2020)
Resistance to current cancer treatments is an important problem that arises through various mechanisms, but one that stands out involves an overexpression of several factors associated with DNA repair. To counteract this type of resistance, different drugs have been developed to affect one or more DNA repair pathways, therefore, to test different compounds of natural origin that have been shown to induce cell death in cancer cells is paramount. Since natural compounds target components of the DNA repair pathways, they have been shown to promote cancer cells to be resensitized to current treatments. For this and other reasons, natural compounds have aroused great curiosity and several research projects are being developed around the world to establish combined treatments between them and radio or chemotherapy. In this work, we summarize the effects of different natural compounds on the DNA repair mechanisms of cancer cells and emphasize their possible application to re-sensitize these cells.